Teutonic Metal: Effects of Place- and Mythology-based Labels on Record Production - Herbst, Jan-Peter (International Journal of the Sociology of Leisure, 2021)
Viking, Mesopotamian and Hellenic metal; place-based metal labels full of mythology are commonplace in metal music. Focusing on ‘Teutonic’ metal, this article analyses such labels through a collaboration with one of the genre’s primary record producers: Karl Bauerfeind. Reflection on sixteen selected album productions with German, British, Swedish and Brazilian bands suggests that imagined communities with symbolic boundaries and shared invented traditions not only shape fan and media discourse but have tangible effects and sonic signatures in record productions, as demonstrated by discussions between bands, producers and record companies. The findings suggest that place- or mythology-based labels evoke vivid, partly fictional, historical inspiration for artists and record producers, which are further negotiated in journalistic media and fan discourse. It is suggested that these imagined communities with respective sonic signatures are both meaningful for fans in their ‘communicative leisure’ practices and used by the music industry as ‘instrumental leisure’ in their marketing efforts.